The SGLT2 inhibitor canagliflozin suppresses lipid synthesis and interleukin-1 beta in ApoE deficient mice. Issue 12 (26th June 2020) - Day, Emily A.; Ford, Rebecca J.; Lu, Jessie H.; Lu, Rachel; Lundenberg, Lucie; Desjardins, Eric M.; Green, Alex E.; Lally, James S.V.; Schertzer, Jonathan D.; Steinberg, Gregory R.
Abstract : Sodium-glucose cotransporter 2 inhibitors such as canagliflozin lower blood glucose and reduce cardiovascular events in people with type 2 diabetes through mechanisms that are not fully understood. Canagliflozin has been shown to increase the activity of the AMP-activated protein kinase (AMPK), a metabolic energy sensor important for increasing fatty acid oxidation and energy expenditure and suppressing lipogenesis and inflammation, but whether AMPK activation is important for mediating some of the beneficial metabolic effects of canagliflozin has not been determined. We, therefore, evaluated the effects of canagliflozin in female ApoE −/− and ApoE −/− AMPK β1 −/− mice fed a western diet. Canagliflozin increased fatty acid oxidation and energy expenditure and lowered adiposity, blood glucose and the respiratory exchange ratio independently of AMPK β1. Canagliflozin also suppressed liver lipid synthesis and the expression of ATP-citrate lyase, acetyl-CoA carboxylase and sterol response element-binding protein 1c independently of AMPK β1. Canagliflozin lowered circulating IL-1β and studies in bone marrow-derived macrophages indicated that in contrast with the metabolic adaptations, this effect required AMPK β1. Canagliflozin had no effect on the size of atherosclerotic plaques in either ApoE −/− and ApoE −/− AMPK β1 −/− mice. Future studies investigating whether reductions in liver lipid synthesis and macrophage IL-1β are important for the cardioprotective effects of canagliflozin warrant further investigation.